Study of Meaning and Function in Koa Baradaik Game in Nagari Duo Koto, West Sumatra - Durin, Hasan Basri (Eduscape : Journal of Education Insight, 2023)
Koa game is one of the activities carried out by Minang men that still exists today. Generally, Koa games are played by four people in pairs (Mandan) in a sitting position and facing each other. In the Koa game, there is a game concept called Baradaik. Koa Baradaik is a form of game based on normative ethics applied in each game. This paper aims to discuss the meaning in the game Koa Baradaik and its correlation to social life. The method used in this paper is a qualitative research method of analysis with an ethnographic approach. The data type consists of primary data and secondary data with data sources consisting of field observations, interviews, and documentation. Data analysis was carried out using normative ethical theory. The results of the study stated that the Koa Baradaik game is a game that adopts the Minangkabau philosophy which aims to bind and prevent deviant behavior by each individual. In addition, Koa baradaik gives birth to functions consisting of (1). Means of thought (2). Koa baradaik becomes a cultural identity in the form of games that contain normative ethics.(3). Koa Baradaik as a means of forming social interaction.